Antibiotic resistance among major pathogens compared to hospital treatment guidelines and antibiotic use in Nordic hospitals 2010–2018. Issue 8 (3rd August 2021) - Möller, Vidar; Östholm-Balkhed, Åse; Berild, Dag; Fredriksson, Mats; Gottfredsson, Magnus; Holmbom, Martin; Järvinen, Asko; Kristjansson, Mar; Rydell, Ulf; Sönksen, Ute Wolff; Kolmos, Hans Joern; Hanberger, Håkan
Abstract: Background: The Nordic countries have comparable nationwide antibiotic resistance surveillance systems and individual antibiotic stewardship programmes. The aim of this study was to assess antibiotic resistance among major pathogens in relation to practice guidelines for hospital antibiotic treatment and antibiotic use in Nordic countries 2010–2018. Methods: Antibiotic resistance among invasive isolates from 2010–2018 and aggregated antibiotic use were obtained from the European Centre for Disease Prevention and Control. Hospital practice guidelines were obtained from national or regional guidelines. Results: Antibiotic resistance levels among Escherichia coli and Klebsiella pneumoniae were similar in all Nordic countries in 2018 and low compared to the European mean. Guidelines for acute pyelonephritis varied; 2nd generation cephalosporin (Finland), 3rd generation cephalosporins (Sweden, Norway), ampicillin with an aminoglycoside or aminoglycoside monotherapy (Denmark, Iceland and Norway). Corresponding guidelines for sepsis of unknown origin were 2nd (Finland) or 3rd (Sweden, Norway, Iceland) generation cephalosporins, carbapenems, (Sweden) combinations of penicillin with an aminoglycoside (Norway, Denmark), or piperacillin-tazobactam (all Nordic countries). Methicillin-resistant Staphylococcus aureus rates were 0–2% and empirical treatment with anti-MRSA antibiotics was not recommended in any country. Rates of penicillin non-susceptibility among Streptococcus pneumoniae were low (<10%) except in Finland and Iceland (<15%), but benzylpenicillin was recommended for community-acquired pneumonia in all countries. Conclusion: Despite similar resistance rates among Enterobacteriaceae there were differences in practice guidelines for pyelonephritis and sepsis. National surveillance of antibiotic resistance can be used for comparison and optimization of guidelines and stewardship interventions to preserve the low levels of antibiotic resistance in Nordic countries.